Speed & Slowness : Deimantas Narkevicius, Michelangelo Pistoletto, Jeff Preis and museum in progress. Chris Dercon and Hans Ulrich Obrist at Galleria Continua. - Dercon, Chris; Obrist, Hans Ulrich; Preis, Jeff; Grazioli, Elio; Galleria Continua, San Gimignano; publieke ruimte, San Gimignano (Prato : Gli Ori, 2003)
Narkevicius, Deimantas ; Pistoletto, Michelangelo ; Preis, Jeff
Deimantas Narkevicius, Michelangelo Pistoletto, Jeff Preis e museum in progress, Galleria Continua, San Gimignano, 10-12-2002 / 1-10-2003
kunstcatalogus
Keywords: San Gimignano